To Identify Myocardial Changes in Severely Malnourished Children: A Prospective Observational Study - Kumar, Neeraj; Pandita, Aakash; Sharma, Deepak; Kumari, Anita; Pawar, Smita; Digra, Kishour Kumar (Frontiers in Pediatrics, 2015)
Abstract Aims and objective: To identify myocardial changes in severely malnourished children. Material and method: This prospective, observational study enrolled 200 children between six months- five years of age who were fulfilling WHO criteria for severe malnutrition. The parents were duly informed and explained about the study and consent was taken. The material for the present study consisted of 200 cases (120 male and 80 female children) suffering from severe protein energy malnutrition according to the mentioned criteria during the period of one year. The age group of the selected cases were divided in five groups viz. <1 years,1-2 years,2-3 years,3-4 years,4-5 years. A random selection of cases was done irrespectively of caste, creed, religion, sex and socioeconomic status etc. Results: 32% cases had flat P-wave on admission, out of which 75%. 84% of cases have increased Q-Tc-Interval at admission. S-T segment was depressed only in 8% of cases. 88% of cases have altered (flat to depressed) T-wave at admission. All of these changes reverted to normal upon nutritional supplementation at discharge. Conclusion: The Electrocardiographic changes may be of help in assessing the severity and prognosis of severe acute malnutrition. The reversal of electrocardiographic changes was observed after dietary therapy. Reversibility of ECG changes suggests that the cardiac changes are not permanent in nature and will not have an effect in adult life. The cardiac status as denoted by heart rate remained same even after a fortnight, suggesting that a prolonged therapy and assessment of cardiac status is warranted even after fortnight therapy.